A study of teachers’ pedagogical content knowledge in Kuningan, West Java - Hanggara, Agie; Darsih, Endang (International Journal of Engineering and Technology, 2019)
The problem of this study is the lack of teachersâ€™ pedagogical content knowledge (PCK), in junior high schools in Kuningan, West Java. Itâ€™s seen from several facts: first, most of social studies teaching process is conducted separately based on each field without any integration;Â second, teachers tend to use monotonous teaching method such as lecturing; third, the lack of ability and skill in using ICT and evaluation system which only focus on studentsâ€™ cognitive aspect. However, teachersâ€™ pedagogical content knowledge is a vital factor in accomplishing successful teaching and learning outcomes to handle existing educational problems. Therefore, it is crucial to investigate the pedagogical content knowledge of social studies teachersâ€™ in Kuningan. In the present study, 164 social studies teachers from 85 junior high schools in Kuningan were surveyed to find out factors influencing teachersâ€™ pedagogical content knowledge.Â The study revealed two important findings: first, teaching experience, training, learning facilities and motivation of teachers have a positive influence on Social Studies teachersâ€™ Pedagogical Content Knowledge (PCK) in Kuningan; second, self efficacy has no influence on Social Studies teachersâ€™ Pedagogical Content Knowledge (PCK) in Kuningan either directly or indirectly.Â Â